INTERNATIONAL EXPERIENCE IN FORECASTING QUALITATIVE CHARACTERISTICS OF THE WORKFORCE - A. A. Tkachenko; A. B. Ginoyan (Финансы: теория и практика, 2017)
The interest in planning the labor force and forecasting its key characteristics such as the education level, qualification, occupation, etc. emerged in the second half of the 20th century. Forecasts provide the basis for the macro-economic policy of the state and choosing optimal directions of development. According to the authors, the quality of the labor force is indispensable for the sustainable development of the national economy and its place in the global market. The prediction of substantial changes in this quality is an integral part of management both in developed and developing economies though in many instances they have different problems to solve. The differences are discussed through the example of forecasting and planning structural changes in the labor force in India, the UK and the USA. The authors substantiate the choice of these countries by the importance of their experience for the Russian practice. The role of international organizations in the development of the methodology for labor force surveys covering approximately 200 countries is analyzed. In the case of India the special role of IT-companies in the development of innovative education systems is revealed which is based on the forward-looking encouraging policy of the state. The analyzed experience is important for Russia, where rural schools and many regions do not have another opportunity to raise the teaching level to the modern requirements. Forecasts of the employment structure in Great Britain and the USA are made by government bodies aided by non-governmental organizations, e. g. the University of Warwick in Great Britain. In the United States government agencies use the macroeconomic model of the Data Resources, Inc. private company for making forecasts. Particular attention is paid to occupation forecasts and vocational training the analysis of which reveals their importance for structural changes in the economy. The analysis of the US forecast as of 2014 for high demand occupations in 2024 highlighted the complexity of determining key indices and methodological approaches to the prediction of employment and the economy demands for qualified personnel in certain professions. The paper assumes that without solving this problem in the Russian management system, no progress in the future growth of the national economy can be expected.